2017
DOI: 10.1038/nclimate3353
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea-ice decline weakens the Atlantic Meridional Overturning Circulation

Abstract: The ongoing decline of Arctic sea ice 1, 2 exposes the ocean to anomalous surface heat and freshwater fluxes, resulting in positive buoyancy anomalies that can affect ocean circulation.In this study, we use an optimal flux perturbation framework and comprehensive climate model simulations to estimate the sensitivity of the Atlantic meridional overturning circulation (AMOC) to such buoyancy forcing over the Arctic and globally, and more generally to sea ice decline. It is found that on decadal timescales flux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
165
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 32 publications
(10 reference statements)
13
165
1
1
Order By: Relevance
“…However, the volcanic forcing is also generally hemispherically symmetric in the high latitudes. However, as other studies have shown, this feedback loop could be sensitive to the mean distribution of sea ice (Sevellec et al, 2017;Zhong et al, 2010) and affected by air-sea interactions (Suo et al, 2017;Zhu et al, 2015). Previous model studies have shown that sea ice expansion in response to the sequence of decadal-spaced volcanic eruptions during the late thirteenth century suppressed deep water formation in the northern North Atlantic, resulting in a weakened AMOC (Slawinska & Robock, 2018;Zhong et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…However, the volcanic forcing is also generally hemispherically symmetric in the high latitudes. However, as other studies have shown, this feedback loop could be sensitive to the mean distribution of sea ice (Sevellec et al, 2017;Zhong et al, 2010) and affected by air-sea interactions (Suo et al, 2017;Zhu et al, 2015). Previous model studies have shown that sea ice expansion in response to the sequence of decadal-spaced volcanic eruptions during the late thirteenth century suppressed deep water formation in the northern North Atlantic, resulting in a weakened AMOC (Slawinska & Robock, 2018;Zhong et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Another positive feedback is the subsequent increase in sea ice cover (Drijfhout, ; Liu et al, ; Vellinga et al, ). The problem of the two‐way interaction between the AMOC and Arctic sea ice and its effect on the AMOC stability is an area of ongoing research (Liu & Fedorov, ; Liu et al, ; Sévellec et al, ; Sun et al, ).…”
Section: Feedbacks Controlling Amoc Stabilitymentioning
confidence: 99%
“…We believe that this review is timely for several reasons. First of all, climate change continues at a relentless pace and strongly affects the freshwater budget of the Arctic and subpolar North Atlantic, for instance, through impacts on sea ice cover (e.g., Sévellec et al, ; Stroeve et al, ), the Greenland Ice Sheet mass balance (e.g., Enderlin et al, ), and enhanced river discharge in the Arctic watershed (e.g., Peterson et al, ). A rigorous assessment of the resilience of the AMOC to these changes is critical, given that the AMOC is thought to be most sensitive to perturbations in the freshwater budget of the subpolar North Atlantic, and such perturbations have been implicated in slowdowns, or even shutdowns, of the AMOC in the past (Lynch‐Stieglitz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Upper layer freshwater in the Arctic Ocean maintains strong near‐surface stratification, which supports Arctic sea ice formation (Aagaard & Coachman, ). Changes in freshwater export from the Arctic could also potentially influence both deep water formation in the North Atlantic and the Atlantic Meridional Overturning Circulation (Aagaard et al, ; Aagaard and Carmack, ; Haak et al, ; Haine et al, ; Holland et al, ; Jahn & Holland, ; Jungclaus et al, ; Nummelin et al, ; Sévellec et al, ; Thornalley et al, ).…”
Section: Introductionmentioning
confidence: 99%